CHLOROPHYLL a FLUORESCENCE ANALYSIS IN FORESTS - Pollastrini, M.; Holland, V.; Brüggemann, W.; Bussotti, F. (Annali di Botanica, 2016)
A European-wide assessment of chlorophyll a fluorescence (ChlF, prompt fluorescence on dark-adapted samples) parameters in forest ecosystems was carried out in the years 2012-2013, within the 7FP FunDivEUROPE project. A total of 1596 trees growing in 209 stands distributed in six countries, from Mediterranean to boreal sites, were sampled. This paper shows the applicability of the ChlF in forest ecology surveys, the protocols adopted for leaf sampling and ChlF measurements, the variability of the ChlF parameters within and between trees, their dependence to environmental factors and the relationships with other functional leaf traits. The most relevant findings were as follows: (i) The least variable ChlF parameter within and between the trees was the maximum quantum yield of primary photochemistry (FV/FM), whereas the performance indices (PIABS and PITOT) showed the highest variability; (ii) for a given tree, the ChlF parameters measured at two heights of the crown (top and bottom leaves) were correlated and, in coniferous species, the ChlF parameters were correlated between different needle age classes (from the current year and previous year); (iii) the ChlF parameters showed a geographical pattern, and the photochemical performance of the forest trees was higher in central Europe than in the edge sites (northernmost and southernmost); and (iv) ChlF parameters showed different sensitivity to specific environmental factors: FV/FM increased with the increase of the leaf area index of stands and soil fertility; ΔVIP was reduced under high temperature and drought. The photochemical responses of forest tree species, analyzed with ChlF parameters, were influenced by the ecology of the trees (i.e. their functional groups, continental distribution, successional status, etc.), tree species’ richness and composition of the stands. Our results support the applicability and usefulness of the ChlF in forest monitoring investigations on a large spatial scale and its possibility of being integrated with remote sensing surveys.